Transgresión del derecho a la estabilidad laboral mínima de las personas con discapacidad, análisis del caso en la ciudad de Machala en el año 2013. - López Apolo, Carlos Andres (2013)
Recognizing the rights to equality and inclusion of persons with disabilities has been a difficult task within the social and legal evolution of Ecuador, due to the fact that historically this group has been lagged behind by the governments of the day, since they are politically unseen As potential voters, however, it is very praiseworthy what is currently being done in terms of the enactment of laws that seek the necessary measures to promote the inclusion of persons with disabilities.